Evaluation of the efficiency of shikimate kinase inactivation in recombinational strains – producers of shikimic acid Вacillus subtilis 168wt21СSA and B. subtilis 5434p4SA - Yu, Chao; Korik, Elena O.; Lahodzich, Aliaksei V. (Experimental Biology and Biotechnology, 2023)
Prototrophic strains Вacillus subtilis 168wt and В. subtilis VKPM 5434 were transformed with recombinational constructs containing the fragment of shikimate kinase gene. The vector constructs were integrated into the bacterial chromosome of the transformed strains via homologous recombination resulting in recombinant strains B. subtilis 168wt21CSA and B. subtilis 5434p4SA. The differences between the obtained strains are due to the mechanism of the shikimate kinase gene inactivation: complete knockout with the construct pMTL21CΔaroK (strain B. subtilis 168wt21CSA) and conditional (IPTG-inducible) expression of shikimate kinase gene with the construct pMUTIN4ΔaroK (strain B. subtilis 5434p4SA). The morphophysiological and biochemical features of the strains В. subtilis 168wt21СSA and В. subtilis 5434p4SA were studied. For both strains under native conditions, the loss of prototrophic properties and the acquisition of ability to increase the synthesis of shikimic acid were noted. For the strain B. subtilis 5434p4SA, the effect of restoring prototrophic properties in some cells of the bacterial population was demonstrated upon activation of the expression of the shikimate kinase gene in the presence of IPTG. The dependence of the change in the number of cells with the activated shikimate kinase gene on the concentration of IPTG inductor in the medium was revealed. Using the HPLC method, we shown that mutant strains synthesise shikimic acid more efficiently than the corresponding parent strains: shikimic acid content in the culture medium can reach 564 µg/mL for the strain B. subtilis 168wt21СSA and 732 µg/mL for the strain B. subtilis 5434p4SA, i. e. more than 2.5 times exceed those for the original strains.
Keywords: Bacillus subtilis; homologous recombination; inactivation of shikimate kinase; the metabolic pathway of shikimat; syntrophism test; IPTG inductor; Pspac promoter